Biosynthesis of rare ketoses through constructing a recombination pathway in an engineered Corynebacterium glutamicum. Issue 1 (10th September 2014) - Yang, Jiangang; Zhu, Yueming; Li, Jitao; Men, Yan; Sun, Yuanxia; Ma, Yanhe
ABSTRACT Rare sugars have various known biological functions and potential for applications in pharmaceutical, cosmetics, and food industries. Here we designed and constructed a recombination pathway in Corynebacterium glutamicum, in which dihydroxyacetone phosphate (DHAP), an intermediate of the glycolytic pathway, and a variety of aldehydes were condensed to synthesize rare ketoses sequentially by rhamnulose‐1‐phosphate aldolase (RhaD) and fructose‐1‐phosphatase (YqaB) obtained from Escherichia coli. A wild‐type strain harboring this artificial pathway had the ability to produce D‐sorbose and D‐psicose using D‐glyceraldehyde and glucose as the substrates. The tpi gene, encoding triose phosphate isomerase was further deleted, and the concentration of DHAP increased to nearly 20‐fold relative to that of the wild‐type. After additional optimization of expression levels from rhaD and yqaB genes and of the fermentation conditions, the engineered strain SY6(pVRTY) exhibited preferable performance for rare ketoses production. Its yield increased to 0.59 mol/mol D‐glyceraldehyde from 0.33 mol/mol D‐glyceraldehyde and productivity to 2.35 g/L h from 0.58 g/L h. Moreover, this strain accumulated 19.5 g/L of D‐sorbose and 13.4 g/L of D‐psicose using a fed‐batch culture mode under the optimal conditions. In addition, it was verified that the strain SY6(pVRTY) meanwhile had the ability to synthesize C4, C5, C6, and C7 rare ketoses when a range of representative achiral and homochiral aldehydes were applied as the substrates. Therefore, the platform strain exhibited the potential for microbial production of rare ketoses and deoxysugars. Biotechnol. Bioeng. 2015;112: 168–180. © 2014 Wiley Periodicals, Inc.